A study to determine an attrativeness of FDI in Malaysia / Nur Najdah Suhaimi - Suhaimi, Nur Najdah (2013)
This study aims to determine whether the three key determinant of FDI is positively related with attractiveness of FDI in Malaysia. For the purpose of the study, the paper uses 30 years of time series data, using FDI inflow focuses on the factors that push in foreign investor to attracted in Malaysian FDI which are natural resources, local business condition and trade openness in Malaysia. The period under study is from 1982-2011. Multiple liner regression analysis is used in the study. The findings reveal that there is a significant impact on natural resources and Trade openness in Malaysia.